IMPLEMENTASI PENGISIAN KEKOSONGAN JABATAN WAKIL KEPALA DAERAH - Ali Ibsan Jaya; Faisal Akbar Nasution; Suhaidi Suhaidi; Mirza Nasution (Universitas Sumatera Utara, 2018)
ABSTRACT The position of the deputy head of the region is very strategic when viewed from the duties and functions of the regional head is so large, So if there is a vacuum of the regional head or deputy head of the region, then the position must be filled immediately. This study is analytical descriptive research. The election of deputy regional head shall be conducted democratically through pairing elections, which is elected in a package of elections as stipulated in the Law on Regional Head Election. Filling the vacancy of the deputy head of the region who is unable to stay under Article 176 of the Law of the Republic of Indonesia Number 10 of 2016 on the Second Amendment to Law Number 1 Year 2015 Concerning the Stipulation of Government Regulation in Lieu of Law No. 1 of 2014 on the Election of Governor, Bupati , And the Mayor becomes the Regulation. Deputy Governor, Vice Regent and Vice Mayor in the event of vacancy, the replacement of Vice Governor, Deputy Regent and Deputy Mayor shall be conducted through election mechanism by Assembly Provincial , Assembly at Regency and City based on the proposal from Political or a combination of Political Which won the election of regional head. Keywords :implementation, vacancy, deputy head of region